2023
DOI: 10.3847/1538-3881/acc336
|View full text |Cite
|
Sign up to set email alerts
|

Planetary Parameters, XUV Environments, and Mass-loss Rates for Nearby Gaseous Planets with X-Ray-detected Host Stars

Abstract: We leverage Gaia DR2 parallactic distances to deliver new or revised estimates of planetary parameters and X-ray irradiation for a distance-limited (≲100 pc) sample of 27 gaseous planets (from super-Earths to hot Jupiters) with publicly available Chandra and/or XMM observations, for which we carry out a homogeneous data reduction. For 20 planets with X-ray-detected host stars we make use of the photoionization hydrodynamics code ATES to derive updated atmospheric mass outflow rates. The newly derived masses/ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 161 publications
0
0
0
Order By: Relevance
“…This yielded a 95% confidence interval on the number of source counts to be [0-11.5], with the upper end of this interval corresponding to a count rate of 0.9 ks −1 . To convert this result to a X-ray flux from WASP-69, we scaled the two-temperature APEC model fit to the 2016 XMM-Newton observation by Spinelli et al (2023b) so that the model Swift count rate indicated by Xspec matched our statistical upper limit for the measured count rate. While X-ray spectral shapes can change with varying flux, especially during flares, we did not detect any flares (see Section 4.2).…”
Section: X-ray Telescope Datamentioning
confidence: 99%
See 2 more Smart Citations
“…This yielded a 95% confidence interval on the number of source counts to be [0-11.5], with the upper end of this interval corresponding to a count rate of 0.9 ks −1 . To convert this result to a X-ray flux from WASP-69, we scaled the two-temperature APEC model fit to the 2016 XMM-Newton observation by Spinelli et al (2023b) so that the model Swift count rate indicated by Xspec matched our statistical upper limit for the measured count rate. While X-ray spectral shapes can change with varying flux, especially during flares, we did not detect any flares (see Section 4.2).…”
Section: X-ray Telescope Datamentioning
confidence: 99%
“…We found the 95% upper limit on the 0.3-2.4 keV unabsorbed flux to be 2.6 × 10 −14 erg cm −2 s −1 . For comparison, the bestfit model published by Spinelli et al (2023b) from XMM-Newton observations in 2016 predicts a flux of -+ 5.19 0.17 0.23 -10 14 erg cm −2 s −1 in the same 0.3-2.4 keV energy range. The archival XMM-Newton flux is 2 times larger than the Swift XRT upper limit from 2023, and we show these data on the timeline in Figure 6.…”
Section: X-ray Telescope Datamentioning
confidence: 99%
See 1 more Smart Citation